Xylem and Leaf Functional Adjustments to Drought in Pinus sylvestris and Quercus pyrenaica at Their Elevational Boundary - Fernández-de-Uña, Laura; Rossi, Sergio; Aranda, Ismael; Fonti, Patrick; González-González, Borja D.; Cañellas, Isabel; Gea-Izquierdo, Guillermo (Frontiers in Plant Science, 2017)
Climatic scenarios for the Mediterranean region forecast increasing frequency and intensity of drought events. Consequently, a reduction in Pinus sylvestris L. distribution range is projected within the region, with this species being outcompeted at lower elevations by more drought-tolerant taxa such as Quercus pyrenaica Willd. The functional response of these species to the projected shifts in water availability will partially determine their performance and, thus, their competitive success under these changing climatic conditions. We studied how the cambial and leaf phenology and xylem anatomy of these two species responded to a 3-year rainfall exclusion experiment set at their elevational boundary in Central Spain. Additionally, P. sylvestris leaf gas exchange, water potential and carbon isotope content response to the treatment were measured. Likewise, we assessed inter-annual variability in the studied functional traits under control and rainfall exclusion conditions. Prolonged exposure to drier conditions did not affect the onset of xylogenesis in either of the studied species, whereas xylem formation ceased one to three weeks earlier in P. sylvestris. The rainfall exclusion had, however, no effect on leaf phenology on either species, which suggests that cambial phenology is more sensitive to drought than leaf phenology. P. sylvestris formed fewer, but larger tracheids under dry conditions and reduced the proportion of latewood in the tree ring. On the other hand, Q. pyrenaica did not suffer earlywood hydraulic diameter changes under rainfall exclusion, but experienced a cumulative reduction in latewood width, which could, however, ultimately challenge its hydraulic performance. The phenological and anatomical response of the studied species to drought is consistent with a shift in resource allocation under drought stress from xylem to other sinks. Additionally, the tighter stomatal control and higher intrinsic water use efficiency observed in drought-stressed P. sylvestris may eventually limit carbon uptake in this species. Our results suggest that both species are potentially vulnerable to the forecasted increase in drought stress, although P. sylvestris might experience a higher risk of drought-induced decline at its low elevational limit.